DERMATOGLYPHICS OF THE CAUCASIANS OF SOUTH IRAN - M.Sharif Kamali (Tehran University of Medical Sciences, 1984)
Bilateral finger and palm prints of 500 males and 500 females of the Caucasian origin in South Iran have been collected and analyzed for both qualitative and quantitative dermatoglyhic features. Results show that most of the qualitative features on bilateral and bisexual differences are not significant. However, quantitative features frequently showed significant differences both bilaterally and bisexually. These results, when, compared with some Indian groups revealed insignificant differences in qualitative dermatoglyphics, while, the quantitative features frequently showed significant differences. The importance of quantitative dermatoglyphic features in population studies has been discussed.